(untitled) (e-Journal of Linguistics, 2018)
The earlier research on critical ecolinguistics tended to criticize the negative impacts of language in encouraging ecologically destructive behavior. However, this present study acts differently, it focusses on analysing positive impacts of language in preserving the environment. This present study aims at analysing the interpretation of ecological preservation revealed in the awig-awig (customary law) text belonging to Tenganan Pegringsingan Village. The data of the research were taken from lexical items, phrases, clauses or sentences used in the written text of the awig-awig. The collected data were analysed using Positive Discourse Analysis (PDA) developed by Stibbe (2017). The findings of the present study showed that the interpretation of ecological preservation in the awig-awig text took the form of preservation of natural ecology, preservation of human ecology, and preservation of spiritual ecology. The three findings above correspond to the Tri Hita Karana (THK) concept which was considered the ecosophy (philosophy of ecological harmony) of the study.